PEMBERDAYAAN ANGGOTA PKK DALAM PELATIHAN PEMBUATAN PROL TAPE DI DESA PENAMBANGAN, KECAMATAN CURAHDAMI, KAPUBATEN BONDOWOSO - Purbasari, Dian; Sofiyah, Siti (LP2M Universitas Jember, 2024)
Penambangan Village is a village located in Curahdami District, Bondowoso Regency. The majority of residents who are members of the Mining Village PKK work as tape sellers. Most of the cassava tape sellers in Mining Village sell the tape directly or in semi-finished condition without processing it into a more attractive product. Seeing these conditions, this community service activity carried out training in making prol tape products for the PKK members of the Mining Village. The aim is to increase the knowledge of the people in the village regarding the processing of tape products and improve skills in making tape diversification into product tape with a higher selling value. This service method is carried out using discussion and practice methods in several stages, namely preparation, implementation of service and evaluation. The result of this community service is that PKK members as training participants in this service program are very enthusiastic in the practice of making prol tape products, apart from that the participants have skills in making prol tape products, so they can continue to produce products that have a higher selling value.